Democratism of Dragojla Jarnević on the Example of her Diary - Odža, Ivana (Poznańskie Studia Slawistyczne, 2019)
The paper analyses, in the context of Dragojla Jarnević’s Diary, the concept of democratism from the authoress’ viewpoint of the world regarding the liberal values that represent foundation of democracy. Considering the problems related to the issue of contemporary democracies eminent intellectuals of the 20th and 21st century have expressed a line of doubts and objections, thereby threatening the concept of democracy, or twisting democracy in its own contradictions. In retrospect, during Dragojla Jarnević’s lifetime and work, there was an evident complexity and ambivalence of disseminating liberal ideas in the area of today´s Croatia. Shaping and expressing of Dragojla Jarnević’s democratic views shows that it is possible to interpret democracy from different points of view – on the one hand, it is the best social model, on the other hand, it sometimes transforms in its contradiction. Certain contradictions are observed in Jarnević’s personality, however, her personality eventually reveals a brave and democratic (literature) subject.